1999
DOI: 10.1212/wnl.53.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of interferon β-1a in chronic inflammatory demyelinating polyradiculoneuropathy

Abstract: This trial shows that IFN-beta is safe but not efficacious in treatment-resistant CIDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(82 citation statements)
references
References 24 publications
1
76
0
5
Order By: Relevance
“…Hadden and colleagues have performed such a study in a randomized double-blinded crossover study of 10 consecutive patients comparing IFN-␤1a versus placebo. 11 One patient improved on IFN-␤, and 2 while receiving placebo. There were no differences in the effect on clinical neurophysiologic measurements.…”
mentioning
confidence: 99%
“…Hadden and colleagues have performed such a study in a randomized double-blinded crossover study of 10 consecutive patients comparing IFN-␤1a versus placebo. 11 One patient improved on IFN-␤, and 2 while receiving placebo. There were no differences in the effect on clinical neurophysiologic measurements.…”
mentioning
confidence: 99%
“…This has also been seen in small pilot studies encompassing sensory-motor, or just motor, progressive or relapsing forms of the disease [9][10] . However, our findings and those of other authors [9][10] are at variance with the results of the unique randomized trial of IFN β1a in CIDP 9 which showed no significant difference between IFN β and a placebo in treated patients, albeit over a shorter follow up period. This difference in the follow up periods might explain the variance in results.…”
Section: Discussionmentioning
confidence: 73%
“…Azathioprine, cyclophosphamide, cyclosporine, interferon-alpha, interferon-beta, mycophenolate mofetil, and methotrexate have all been reported to be beneficial in CIDP patients not responsive to initial therapies [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108]. For the most part, these studies were not prospective, randomized, or blinded.…”
Section: Treatmentmentioning
confidence: 99%
“…A negative randomized controlled trial of oral methotrexate 15 mg weekly was reported in CIDP [109]. A recent studied evaluating the effects of intramuscular interferon-beta-1a (Avonex) at low (30 micrograms weekly), intermediate (30 micrograms twice weekly or 60 micrograms weekly) and high dose (60 micrograms twice weekly) on IVIg dose in CIDP did not show a significant benefit [104,105,110]. High dose cyclophosphamide without stem cell rescue can lead to long-term remission with refractory CIDP [97] with improved quality of life [112].…”
Section: Treatmentmentioning
confidence: 99%